2021
DOI: 10.3389/fanim.2021.758165
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Behavior and Posture Detection of Sows in Loose Farrowing Pens Based on 2D-Video Images

Abstract: The monitoring of farm animals and the automatic recognition of deviant behavior have recently become increasingly important in farm animal science research and in practical agriculture. The aim of this study was to develop an approach to automatically predict behavior and posture of sows by using a 2D image-based deep neural network (DNN) for the detection and localization of relevant sow and pen features, followed by a hierarchical conditional statement based on human expert knowledge for behavior/posture cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In the study of Küster et al [ 25 ], YOLOv3 was used to detect different parts of sows’ bodies in farrowing pens, i.e., heads, tails, legs, and udder, but not the whole sows’ bodies, as in our study. They detected heads with 97 AP 50 , tails with 78 AP 50 , legs with 75 AP 50 and udder with 66 AP 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Küster et al [ 25 ], YOLOv3 was used to detect different parts of sows’ bodies in farrowing pens, i.e., heads, tails, legs, and udder, but not the whole sows’ bodies, as in our study. They detected heads with 97 AP 50 , tails with 78 AP 50 , legs with 75 AP 50 and udder with 66 AP 50 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the speed of YOLOX was from 21 fps with YOLOX-extra large to 42 fps with YOLOX-nano. A comparison to YOLOv3 in the research of Küster et al [ 25 ] and van der Zande et al [ 26 ] was not possible as the speed of inference of YOLOv3 was not reported by the authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also a multi-pig trajectory tracking model based on DeepLabCut was described, but only in younger growing pigs [42]. Images were collected from either crated sows [38,43,45] or loose-housed sows [8,44] either before farrowing [46], during farrowing [38] or during lactation [8,[43][44][45]. In these studies, either a 2D RGB-camera [38,44,46] or 3D Kinetic camera [8,43,45] was used.…”
Section: Sow Pose Estimationmentioning
confidence: 99%
“…Here, the most frequently used detection approaches aim to localize an object of interest by computing a bounding box around the object [19][20][21]. Although these approaches work successfully for various problem settings, due to the overlapping of the predicted bounding boxes, their applicability is limited for the analysis of videos with high utilization rates and several pigs in a close environment [22,23]. Furthermore, the standard bounding box approach only provides the positional information without taking the orientation of the animal into account which is a key information in order to reliably differentiate distinctive contact types like head-head interactions.…”
Section: Introductionmentioning
confidence: 99%